2017
DOI: 10.1016/j.joa.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of pericardial effusion as an early complication of catheter ablation for atrial fibrillation: The Japanese Catheter Ablation Registry of Atrial Fibrillation (J‐CARAF)

Abstract: BackgroundPericardial effusion (PE) is one of the most frequent complications from catheter ablation of atrial fibrillation (AF). We assessed the prevalence and predictive factors of PE that require invasive treatment as an early complication of AF ablation.MethodsThe Japanese Heart Rhythm Society requested electrophysiology centers to register the relevant data of patients who underwent AF ablation during 6 months from 2011 to 2015. We compared the clinical profiles and the procedures of AF ablation between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…They showed that use of three-dimensional mapping system and use of novel oral anticoagulants are independent predictors of lower incidence of pericardial effusion. Repeat ablation procedures were included in the analysis but they did not find significant difference regarding the incidence of pericardial effusion between initial and repeated ablation procedures 14 . Their statistical analysis investigated pericardial effusions only, which might be an explanation why these results does not converge with our findings.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…They showed that use of three-dimensional mapping system and use of novel oral anticoagulants are independent predictors of lower incidence of pericardial effusion. Repeat ablation procedures were included in the analysis but they did not find significant difference regarding the incidence of pericardial effusion between initial and repeated ablation procedures 14 . Their statistical analysis investigated pericardial effusions only, which might be an explanation why these results does not converge with our findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Recent studies reported various predictors of complications, however, most of them were derived from cohorts where only first ablation procedures were included 2 , 4–14 . Therefore limited data exist regarding the role and predictive value of a repeat procedure on procedural outcomes 2 , 11 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Deep sedation, reduced left ventricular function, warfarin, AF, and female sex have been reported as risk factors for PE. 2 , 10 Of these 5 risks, they distributed from 0 to 3 points in this study. Another paper reported that no significant factors are associated with the occurrence of tamponade, including age, body mass index, sex, AF type, left atrial dimension, use of an RF needle, operators, peak ACT, and direct oral anticoagulant use except for the use of a cryoballoon.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion (PE) due to cardiac perforation is a known major complication of radiofrequency (RF) catheter ablation (CA). The reported incidence of PE during CA was 0.5%–4.0% for atrial fibrillation (AF) 1 , 2 and 2% for ventricular tachycardia (VT). 3 , 4 It can be caused by mechanical trauma during catheter manipulation, inadvertent injury during transseptal puncture, or steam pop during CA.…”
Section: Introductionmentioning
confidence: 99%
“…This registry included cases performed not only in high-volume centers but also low-volume ones and published reports continuously. [5][6][7][8][9][10][11][12] However, this registry included exclusively AF ablation cases performed in September and features of other arrhythmias were not investigated. In contrast to these preceding registries, the current J-AB registry is taking a step forward since it is aiming to collect all catheter ablation cases performed in one country, from various types of centers (small-and largevolume centers), to reveal the current real-world status of catheter ablation in Japan.…”
Section: Discussionmentioning
confidence: 99%